Metabolism and Occurrence of Methanogenic and Sulfate-Reducing Syntrophic Acetate Oxidizing Communities in Haloalkaline Environments - Timmers, Peer H. A.; Vavourakis, Charlotte D.; Kleerebezem, Robbert; Damsté, Jaap S. Sinninghe; Muyzer, Gerard; Stams, Alfons J. M.; Sorokin, Dimity Y.; Plugge, Caroline M. (Frontiers in Microbiology, 2018)
Anaerobic syntrophic acetate oxidation (SAO) is a thermodynamically unfavorable process involving a syntrophic acetate oxidizing bacterium (SAOB) that forms interspecies electron carriers (IECs). These IECs are consumed by syntrophic partners, typically hydrogenotrophic methanogenic archaea or sulfate reducing bacteria. In this work, the metabolism and occurrence of SAOB at extremely haloalkaline conditions were investigated, using highly enriched methanogenic (M-SAO) and sulfate-reducing (S-SAO) cultures from south-eastern Siberian hypersaline soda lakes. Activity tests with the M-SAO and S-SAO cultures and thermodynamic calculations indicated that hydrogen and formate are important IECs in both SAO cultures. Metagenomic analysis of the M-SAO cultures showed that the dominant SAOB was ‘Candidatus Syntrophonatronum acetioxidans’, and a near-complete draft genome of this SAOB was reconstructed. ‘Ca. S. acetioxidans’ has all genes necessary for operating the Wood-Ljungdahl pathway, which is likely employed for acetate oxidation. It also encodes several genes essential to thrive at haloalkaline conditions; including a Na+-dependent ATP synthase and marker genes for ‘salt-out‘ strategies for osmotic homeostasis at high soda conditions. Membrane lipid analysis of the M-SAO culture showed the presence of unusual bacterial diether membrane lipids which are presumably beneficial at extreme haloalkaline conditions. To determine the importance of SAO in haloalkaline environments, previously obtained 16S rRNA gene sequencing data and metagenomic data of five different hypersaline soda lake sediment samples were investigated, including the soda lakes where the enrichment cultures originated from. The draft genome of ‘Ca. S. acetioxidans’ showed highest identity with two metagenome-assembled genomes (MAGs) of putative SAOBs that belonged to the highly abundant and diverse Syntrophomonadaceae family present in the soda lake sediments. The 16S rRNA amplicon datasets of the soda lake sediments showed a high similarity of reads to ‘Ca. S. acetioxidans’ with abundance as high as 1.3% of all reads, whereas aceticlastic methanogens and acetate oxidizing sulfate-reducers were not abundant (≤0.1%) or could not be detected. These combined results indicate that SAO is the primary anaerobic acetate oxidizing pathway at extreme haloalkaline conditions performed by haloalkaliphilic syntrophic consortia.